In-Context Learning Unlocked for Diffusion Models - Wang, Zhendong; Jiang, Yifan; Lu, Yadong; Shen, Yelong; He, Pengcheng; Chen, Weizhu; Wang, Zhangyang; Zhou, Mingyuan (NeurIPS 2023, 2023)
We present Prompt Diffusion, a framework for enabling in-context learning in diffusion-based generative models. Given a pair of task-specific example images, such as depth from/to image and scribble from/to image, and a text guidance, our model automatically understands the underlying task and performs the same task on a new query image following the text guidance. To achieve this, we propose a vision-language prompt that can model a wide range of vision-language tasks and a diffusion model that takes it as input. The diffusion model is trained jointly over six different tasks using these prompts. The resulting Prompt Diffusion model is the first diffusion-based vision-language foundation model capable of in-context learning. It demonstrates high-quality in-context generation on the trained tasks and generalizes effectively to new, unseen vision tasks with their respective prompts. Our model also shows compelling text-guided image editing results. Our framework, with code publicly available at this https URL, aims to facilitate research into in-context learning for computer vision.